2016
DOI: 10.1123/jpah.2016-0369
|View full text |Cite
|
Sign up to set email alerts
|

Results From Colombia’s 2016 Report Card on Physical Activity for Children and Youth

Abstract: Background:Physical activity (PA) is vital to the holistic development of young people. Regular participation in PA is associated with substantial benefits for health, cognitive function, and social inclusion. Recognizing the potential of PA in the context of the current peace process in Colombia, the purpose of this article is to present the methodology and results of Colombia’s second Report Card on PA for children and youth.Methods:A group of experts on PA graded 14 PA indicators based on data from national… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 19 publications
(28 reference statements)
1
20
0
1
Order By: Relevance
“…In that study, the author found that the BMI values of girls were considerably higher than those of boys. Furthermore, the tendencies regarding obesity status reported in our study are also in consonance with the general statistics of Colombia’s 2016 Report Card on physical activity for children and youth [ 24 ]. These research results justify the need to implement programs that foment healthy life styles from an early age.…”
Section: Discussionsupporting
confidence: 90%
“…In that study, the author found that the BMI values of girls were considerably higher than those of boys. Furthermore, the tendencies regarding obesity status reported in our study are also in consonance with the general statistics of Colombia’s 2016 Report Card on physical activity for children and youth [ 24 ]. These research results justify the need to implement programs that foment healthy life styles from an early age.…”
Section: Discussionsupporting
confidence: 90%
“…[37][38][39][40][41] In addition, studies on sedentary behaviors have also found that Colombian children have high levels of sedentary behaviors with about 50% of children spending 2 or more hours per day watching TV. 39,42 Furthermore, these studies, along with some in other countries, have also found a positive relationship between sedentary behaviors and overweight/obesity status in children, where children who spend more time watching TV have increased odds of being overweight/obese. 39,[43][44][45]…”
Section: Discussionmentioning
confidence: 78%
“…Several previous analyses of children in Colombia have also found that most children in the country are not engaged in sufficient levels of physical activity and few meet WHO recommendations for physical activity (at least 60 minutes per day, every day) . In addition, studies on sedentary behaviors have also found that Colombian children have high levels of sedentary behaviors with about 50% of children spending 2 or more hours per day watching TV . Furthermore, these studies, along with some in other countries, have also found a positive relationship between sedentary behaviors and overweight/obesity status in children, where children who spend more time watching TV have increased odds of being overweight/obese …”
Section: Discussionmentioning
confidence: 92%
“…29,30 The difference between the sexes found in the present study could be related to the fact that girls usually have lower physical activity levels than boys, as reported in the latest results from Colombia's 2016 Report Card on Physical Activity for Children and Youth. 31 For this reason, AST could be sufficient to promote improvements in girls' physical fitness.…”
Section: Discussionmentioning
confidence: 99%